An Extended Study on Tense and Aspect Markers in Pagu - Dalan Mehuli Perangin Angin (Universitas Sanata Dharma, 2022)
This paper revisits four clitics of Pagu (a West-Papuan language spoken in North Halmahera, Indonesia) those that have been described as Tense and Aspect markers (Wimbish 1991): -oka, -ou -osi, and -uli. The first one is considered a tense marker for ‘non-future’ time, while the other three are aspect markers for ‘perfective’, ‘imperfective’, and ‘repetitive’ respectively. Following a metatypy approach (Ross 2006; 2001), I argue that while these clitics have the tense-aspect functions, at the same time under a unified analysis, each should have an extended function vis. a ‘locational marker of space and time’, ‘confirmative’, ‘durative’, and ‘repetitive presupposition marker’, respectively. These meanings and functions are based on the speakers’ interpretation of them in the local lingua franca (a variety of the North Maluku Malay). This supports Bowden’s (2012) argument that the indigenous languages of North Halmahera (Papuan) have influenced the present varieties of Malay spoken as the lingua franca in the region.